Acute Benign Childhood Myositis Due to Bartonella henselae: A Rare Pathogen: Miositis aguda benigna infantil por Bartonella henselae: un patógeno infrecuente | 由巴尔通氏菌（Bartonella henselae）引起的急性良性儿童肌炎：一种罕见病原体 - Paz-Vargas, José (2024)
Acute benign myositis of childhood (ABIM) is an inflammatory pathology of the musculoskeletal system, it usually manifests with pain in the lower limbs associated with elevation of creatine phosphokinase (CPK). It is a rare condition, but if it occurs, it appears after a flu case, frequently associated with influenza A and B viruses. The case of a school-age girl with myalgia in lower limbs, fever and elevated CPK, diagnosed with MABI, with positive IgG to Bartonella henselae. It is considered important to report the case due to the little information available about this disease both in the country and in Latin America, in addition, to review the issue since there are no previous reports in Peru about Bartonella henselae as the etiological agent of MABI; Likewise, discuss management and how to reduce unnecessary hospitalizations.